Analyzing an Implementation of Patient Safety Targets Standards at Ja'far Medika Hospital Based on Hospital Accreditation National Standards (SNARS) Issue 1.1 - Angga Suryawinata; Sri Sundari; Qurratul Aini (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Background: The complexity of hospital operations has the errors’ potential. Patient safety will have an impact on the patient's medical condition as well as increasing health costs. Ja'far Medika Hospital scored 82.4 in the KARS accreditation survey using SNARS edition 1.1 in 2019. This study analyzes the implementation of patient safety target standards at Ja'far Medika Hospital Karanganyar based on SNARS edition 1.1. Methods: This study is a quantitative descriptive study by document review, observation of infrastructure facilities, and observation of the implementation of patient safety at Ja'far Medika Hospital. Results and discussion: The accomplishment of the implementation of patient safety goals that meet the passing grade are the accuracy of identifying patient by 85%, reducing the risk of infection related to health services/healthcare-acquired infections (HAIs) by 82.3%, and reducing the risk of injury due to falls by 87.5%. Whereas the targets below the passing grade are improve effective communication by 78.5%, Increased safety of high alert medication (HAM) by 75%, and the confirmation of the exact location, procedure, and patient of the operation by 50%. Conclusion: The implementation of patient safety targets at Ja'far Medika Hospital has not been carried out optimally with the target of Effective Communication improvement, the safety enhancement of high alert drugs/drugs that need to watched out and the confirmation of the exact location, procedure, and patient of the operation